Anthelmintic Drugs for Repurposing against Gram-Negative Bacilli Infections - Canturri, Andrea Miró; Smani, Younes (Current Medicinal Chemistry, 2023)
Bacterial infections are among the leading causes of death worldwide. The emergence of antimicrobial resistance factors threatens the efficacy of all current antimicrobial agents, with some already made ineffective, and, as a result, there is an urgent need for new treatment approaches. International organizations, such as the World Health Organization and the European Centre for Diseases Control, have recognized infections caused by multi-drug-resistant (MDR) bacteria as a priority for global health action. Classical antimicrobial drug discovery involves in vitro screening for antimicrobial candidates, Structure-Activity Relationship analysis, followed by in vivo testing for toxicity. Bringing drugs from the bench to the bedside involves huge expenditures in time and resources. This, along with the relatively short window of therapeutic application for antibiotics attributed to the rapid emergence of drug resistance, has, at least until recently, resulted in a waning interest in antibiotic discovery among pharmaceutical companies. In this environment, “repurposing” (defined as investigating new uses for existing approved drugs) has gained renewed interest, as reflected by several recent studies, and may help to speed up the drug development process and save years of expensive research invested in antimicrobial drug development. The goal of this review is to provide an overview of the scientific evidence on potential anthelmintic drugs targeting Gram-negative bacilli (GNB). In particular, we aim to: (i) highlight the potential of anthelmintic drugs for treatments of GNB infections, (ii) review their mechanisms of action against these bacteria, (iii) summarize the outcome of preclinical studies investigating approved anthelmintic drugs that target these bacteria, (iv) provide critical challenges for further anthelmintic repurposing drugs development, and (v) list the specific anthelmintic drugs that may be more likely to be repurposed.
Keywords: bacteria